1977
DOI: 10.1177/003693307702200117
|View full text |Cite
|
Sign up to set email alerts
|

Observations in Man of Hypoglycaemia during Selective and Non-Selective Beta-Blockade

Abstract: The acute hypoglycaemic reaction is accompanied by a rise in systolic and a slight fall in diastolic blood pressure and a tachycardia. In contrast, during beta-blockade with propranolol there is a rise of both systolic and diastolic blood pressures and bradycardia. Restoration of blood glucose to normal is delayed. With metoprolol there is a lesser increase in diastolic blood pressure and a slight tachycardia. Restoration of the blood glucose to normal is little delayed. When patients liable to hypoglycaemia r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

1978
1978
2000
2000

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(15 citation statements)
references
References 9 publications
2
13
0
Order By: Relevance
“…Our cardiovascular findings corroborate those of previous studies (Davidson et al, 1977;Lager et al, 1979;Lloyd-Mostyn & Oram, 1975). The decreased pulse rates, during hypoglycaemia, whilst the subjects were taking propranolol or atenolol, suggests that their ,3-adrenoceptors were well blocked at the time of study.…”
Section: Discussionsupporting
confidence: 91%
“…Our cardiovascular findings corroborate those of previous studies (Davidson et al, 1977;Lager et al, 1979;Lloyd-Mostyn & Oram, 1975). The decreased pulse rates, during hypoglycaemia, whilst the subjects were taking propranolol or atenolol, suggests that their ,3-adrenoceptors were well blocked at the time of study.…”
Section: Discussionsupporting
confidence: 91%
“…Then, unopposed a-adrenoceptor stimulation from adrenaline release results in a marked diastolic pressor effect, which triggers a bradycardia via the baroreceptors (Davidson et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the use of selective P-blockers may circumvent this problem [10]. However, reports on the effects of propranolol and metoprolol on glucose metabolism during insulin-induced hypogly cemia have been contradictory [11][12][13][14] and no study in hemodialysis patients has been reported.…”
Section: Introductionmentioning
confidence: 99%